Strategi Pembelajaran Teori Behavioristik Conditioning oleh Edwin Guthrie dan Watson dalam Meningkatkan Motivasi Belajar IPAS Siswa Kelas 4 Sekolah Dasar - Ritzki Wedanthi, Luh Putu; Suarni, Ni Ketut; Margunayasa, I Gede (Universitas Batanghari Jambi, 2025)
This research is an experimental research with a Nonequivalent Pretest Posttest Control Group Design. The research subjects consisted of 4th grade elementary school students who were divided into experimental groups & control groups using the Cluster R&om Sampling Technique. Data collection was carried out through the IPAS learning motivation test with validated instruments. Data analysis used the Polled Variance T test to ensure data homogeneity. The results of the research showed that there was a significant increase in the science learning motivation of grade 4 students who applied the Behavioristic Conditioning Theory Learning Strategy. Thus, it can be said that the application of this strategy has a positive influence on student learning motivation.